Sustainable Development of Tourism under the Background of Low-Carbon and Green Economy - Lirong Han; Lei Li (Advances in Materials Science and Engineering)
The development of tourism industry not only promotes social and economic progress and the improvement of people’s happiness index but also causes resource damage and environmental pollution, which not only affects our living environment but also directly threatens the survival and development of mankind. Therefore, how tourism will develop in the context of low-carbon green economy has become the main problem of tourism development. Based on the above background, in order to solve the development problem of tourism in the future under the low-carbon green economy, based on the research results at home and abroad, starting from the starting point of sustainable development of tourism, this paper introduces the concept of “tourism consumption separation rate” and uses Kaya traditional accounting method. The structural decomposition analysis method and cointegration relationship test method are used to calculate, analyze, and test the tourism carbon emissions and influencing factors at the overall level of China and the middle, western, and eastern regions. Through this method, the accuracy of the calculation results is improved by 30%, which increases the accuracy of the experimental data and is more practical.